Accuracy of the digital workflow for guided insertion of orthodontic palatal TADs: a step-by-step 3D analysis - Lucia Pozzan; Marco Migliorati; Luca Dinelli; Riccardo Riatti; Lucio Torelli; Roberto Di Lenarda; Luca Contardo (SpringerOpen, 2022)
Abstract Background The introduction in the orthodontic field of the digital workflow for guided insertion of palatal TADs and the development of the 1-visit protocol led to the reduction of chair time and the possibility of complete customization of designs and materials. Conversely, the reduction of operative steps implicates a lower tolerance of deviations between the planned and the actual position of the miniscrews, particularly when the orthodontic device is fixed on 4 palatal TADs or has a rigid structure. This study aims to analyze the influence of each step of the digital workflow on the deviation of the miniscrews' axis of insertion in a bicortical sample. The null hypothesis is that there are no significant differences in the deviations among the operative steps. Methods 33 subjects were selected for insertion of bicortical palatal miniscrews with a 1-visit protocol. Digital files were collected at the three stages of the workflow (i.e., digital planning, laboratory prototype, post-insertion impression). A 3D software analysis was performed on a total of 64 miniscrews. After automatic shape recognition of the guiding holes of the digital plan and the scanbodies of the laboratory prototype and post-insertion impression as geometric cylinders, their three-dimensional longitudinal axis was traced and the deviation among them was calculated. Friedman test with Bonferroni correction was performed to assess the significance of the deviations among the three steps, with significance set at p < 0.05. Results The laboratory step has a significantly lower degree of deviations (2.12° ± 1.62) than both the clinical step (6.23° ± 3.75) and the total deviations (5.70° ± 3.42). No significant differences were found between miniscrews inserted on the left or the right side. Conclusions This study suggests that laboratory procedures such as surgical guide production or rapid prototyping don't play a significant role in the degree of deviations between the planned and the positioned palatal TADs. Conversely, the clinical steps have a bigger influence and need to be carefully evaluated. Despite this difference, there is a cumulative effect of deviations that can lead to the failure of the 1-visit protocol.